Pengaruh penambahan tepung sortgum dan bit root terhadap karakteristik flake - Nur Fitri Hidayati; Muh. Aniar Hari Swasono (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
One of the potential dry land food plants developed in Indonesia is sorghum. Sorghum is a kind of grass crop and is still a family with rice, corn and wheat. The carbohydrate content in the seeds is quite high, so it can be consumed as staple food, along with the development of many innovations that are done to make this plant to be better known and in the community's favor, one of the processed sorghum is Flakes, Sorghum Flakes is a processed food based on sorghum with the addition of beetroot root, sugar, salt and water. This study aims to determine the effect of the addition of sorghum flour (30 gr, 60 gr, 90 gr) and beetroot flour (5 gr, 10gr, 15 gr) to the characteristics of Flakes, Organoleptic parameters were analyzed statistically using the Fridmen test while to find out the best treatment in the test Organoleptic tests were carried out on the effectiveness index test, the experimental design used the Completely Randomized Design (CRD) method with 2 factors and 3 repetitions. The best treatment is determined by the effectiveness index test with the calculation results show the best treatment is on S2B2 with a formulation of 60gr sorghum flour and 10gr beetroot flour